Changing substrate specificity and iteration of amino acid chain elongation in glucosinolate biosynthesis through targeted mutagenesis of Arabidopsis methylthioalkylmalate synthase 1. Issue 7 (2nd July 2019) - Petersen, Annette; Hansen, Lea Gram; Mirza, Nadia; Crocoll, Christoph; Mirza, Osman; Halkier, Barbara Ann
Abstract : Methylthioalkylmalate synthases catalyse the committing step of amino acid chain elongation in glucosinolate biosynthesis. As such, this group of enzymes plays an important role in determining the glucosinolate composition of Brassicaceae species, including Arabidopsis thaliana . Based on protein structure modelling of MAM1 from A. thaliana and analysis of 57 MAM sequences from Brassicaceae species, we identified four polymorphic residues likely to interact with the 2-oxo acid substrate. Through site-directed mutagenesis, the natural variation in these residues and the effect on product composition were investigated. Fifteen MAM1 variants as well as the native MAM1 and MAM3 from A. thaliana were characterised by heterologous expression of the glucosinolate chain elongation pathway in Escherichia coli . Detected products derived from leucine, methionine or phenylalanine were elongated with up to six methylene groups. Product profile and accumulation were changed in 14 of the variants, demonstrating the relevance of the identified residues. The majority of the single amino acid substitutions decreased the length of methionine-derived products, while approximately half of the substitutions increased the phenylalanine-derived products. Combining two substitutions enabled the MAM1 variant to increase the number of elongation rounds of methionine from three to four. Notably, characterisation of the native MAMs indicated that MAM1 and not MAM3 is responsible for homophenylalanine production. This hypothesis was confirmed by glucosinolate analysis in mam1 and mam3 mutants of A. thaliana .